Excitation and time resolved spectroscopy of SAW harmonics up to GHz regime in photolithographed GaAs devices. (27th October 2017) - Rizzato, Silvia; Scigliuzzo, Marco; Chiriacò, Maria Serena; Scarlino, Pasquale; Monteduro, Anna Grazia; Maruccio, Claudio; Tasco, Vittorianna; Maruccio, Giuseppe
Abstract: In this work, we demonstrate the excitation of surface acoustic waves (SAW) harmonics up to GHz regime in photolitographed devices fabricated on gallium arsenide (GaAs) by acting on the IDT metallization ratio among the finger width and pitch. Specifically, we observed up to the 13th harmonic, which corresponds to a frequency of about 1.7 GHz. Moreover, we employed time-resolved spectroscopy for isolating the shape of the SAW bandpass-filter response (for each harmonic) eliminating the interference between acoustic and electromagnetic waves. Notably, the extracted SAW spectra are characterized by a bandwidth which remains constant for the different harmonic modes, unlike the case of traditional SAW filters (having a 0.5 metallization ratio) where the pass band Δ f = f 0 n p increases with the working frequency. These results are relevant for applications where high frequencies and multiple harmonics excitation are desirable, or where quantitative measurements of the direct SAW signal are required.